Implementation of the Regent Regulation of Pasuruan Number 27 of 2023 concerning the Strategic Plan of the Pasuruan Regency Manpower Office for the Years 2024–2026 in the Perspective of Public Choice - Hambali (International Publisher, 2025)
This study aims to analyze the implementation of the Regent Regulation of Pasuruan Number 27 of 2023, which outlines the Strategic Plan of the Pasuruan Regency Manpower Office for the years 2024–2026, through the lens of Public Choice theory. The research adopts a qualitative descriptive method, focusing on understanding how individual interests and institutional dynamics influence policy execution. The population comprises stakeholders involved in the formulation and implementation of the strategic plan, including government officials, labor organizations, and community representatives. A purposive sampling technique is employed to select key informants who provide in-depth insights into the policy processes. Data collection instruments include semi-structured interviews, document analysis, and observation. The findings reveal that the implementation of the strategic plan is significantly influenced by the interplay of various interest groups, leading to potential elite capture and deviations from the intended policy objectives. The study underscores the necessity for enhanced transparency, stakeholder engagement, and accountability mechanisms to align the strategic plan's execution with the broader public interest.